Running intensity fluctuations indicate temporary performance decrement in top-class football. Issue 1 (2nd January 2017) - Fransson, Dan; Krustrup, Peter; Mohr, Magni
ABSTRACT: Match analyses were performed on 473 top-class male footballers. Distances covered during peak-distance 1-, 2- and 5-min periods of a game were 98 ± 5, 135 ± 8 and 235 ± 13 m at speeds >14 km·h −1 . In the 5-min period following peak-distance 1-, 2- and 5-min periods, players had a high-intensity running distance deficit ( P < 0.05) of 21, 18 and 17 m, respectively, compared to average 5-min distance. High-intensity running distances covered in peak-distance 5- and 1-min periods were greater ( P < 0.05) for all playing positions other than central defender. In the 5-min period following the peak-distance 5-min period, less ( P < 0.05) high-intensity distance was covered for all playing positions than in the average 5-min period. Distances covered by substitutes during the last 15 min of a game at speeds >11->24 km·h −1 were greater (18–39%; P < 0.05) compared to full-game players. In 5-min period following peak-distance 1-, 2- and 5-min periods, substitutes performed 9–21% less high intensity running than on average. In conclusion, peak-distance 1-, 2- and 5-min periods in a top-class football game reduce high-intensity running distance in the following 5-min period for all playing positions in both full-game players and substitutes. Thus, these short-term periods of a game may induce temporary performance decrement in top-class football players.